2018
DOI: 10.1002/etep.2533
|View full text |Cite
|
Sign up to set email alerts
|

Automatic generation control of an interconnected CCGT-thermal system using stochastic fractal search optimized classical controllers

Abstract: Summary During the past few decades, frequency regulation of combined cycle gas turbine (CCGT) has become an interesting issue of research. A larger power system model experiences many challenges when base‐loaded CCGT unit is incorporated in it. This article presents the load frequency regulation of CCGT model in conjunction with thermal units in an unequal 3‐area interconnected system. The control strategy of CCGT plant includes temperature and air flow controllers that are designed on the basis of minimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…They also considered GRC with nonlinearity in their work. Saha et al reported the use of stochastic fractional search algorithm for the LFC of MAPS that included a thermal power plant [37]. Raju et al reported the issue of LFC of MAPS with distributed generation resources, using a hybrid Ant-Lion Optimizer (ALO) pattern search optimization technique [38].…”
Section: Lfc In a Maps With Conventional Sourcesmentioning
confidence: 99%
“…They also considered GRC with nonlinearity in their work. Saha et al reported the use of stochastic fractional search algorithm for the LFC of MAPS that included a thermal power plant [37]. Raju et al reported the issue of LFC of MAPS with distributed generation resources, using a hybrid Ant-Lion Optimizer (ALO) pattern search optimization technique [38].…”
Section: Lfc In a Maps With Conventional Sourcesmentioning
confidence: 99%
“…Most of the literature on LFC studies reported so far had considered step-load perturbations, and few works reported with specific random load perturbation (RLP). 27,28 Since the net linear load (LL) demand variation (ΔP LL ) of hμG varies rapidly in a real-world scenario, hence a specific RLP pattern is instigated for 12 time slots of 10-second durations considering the monthly domestic metering of an average consumer in Bhubaneswar from January to December 2017, and listed in Table 1. Sometimes, nonlinearities are included in the system due to collective effects of some nonlinear loads, grid-tied-converters, and semiconductor-switching devices etc.…”
Section: Data Acquisition For Res and Load Demandmentioning
confidence: 99%
“…However, the coordinated frequency and voltage regulation of a 50‐Hz frequency‐based isolated hμG are unexplored so far. Again, most of the earlier works 27‐29 are focused on active power balance of a 60‐Hz–based system with ALFC, whereas this work focuses on apparent power balance introducing a novel integral square of weighted absolute error function (ISWAE). Hence, this work is motivated towards putting an earliest effort to study the performances of proposed (50‐Hz–based) hμG with PID controllers, using a novel QSHO algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review discloses that numerous control techniques have been reported to take care of the LFC problem, such as self‐tuning based controller, 2 conventional controllers, 4‐12 fuzzy logic based controller, 13‐17 robust adaptive controller, 18 sliding mode controller, 19‐21 ANFIS based controller, 22 minimal‐order observer‐based controller, 23,24 and so on. A comprehensive state‐of‐the‐art on the LFC mechanism for power systems is reported in Reference 25.…”
Section: Introductionmentioning
confidence: 99%